A Dictionary of English Rhyming Slangs - Lillo Buades, Antonio (Topics in English Linguistics TiEL, 2017)
This reference work addresses a long-standing need in the study of a class of lexis which attracts attention from scholars and the general public alike. Based on years of extensive research, the dictionary presents a satisfying collection of the varieties of rhyming slang found in and around English-speaking communities worldwide. It covers all forms of rhyming slang in the anglophone world by users from differing social groups and walks of life: criminals, musicians, anglers, second-hand car dealers and sheep-shearers, among many others. Besides ordinary lexical items, this work also lists nicknames and one-off expressions found in culturally valued works, from the fields of literary fiction, poetry, comics, TV and radio series, and films. Each entry is accompanied by chronologically ordered citations from a wide variety of sources (printed and otherwise) showing a word's life and currency. The scope, size and approach of this significant compilation, supported by a substantial bibliography, make it an indispensable work of reference for anyone with an interest in English slang and a key starting point for future research on the origins, social history and development of this fascinating area of the English lexicon.